Identification of nursing assessment models/tools validated in clinical practice for use with diverse ethno-cultural groups: an integrative review of the literature - Ortiz Lucenia; Mogale Ramadimetja S; Richter Magdalena S; Higginbottom Gina MA; Young Susan; Mollel Obianuju (BMC, 2011)
Abstract Background High income nations are currently exhibiting increasing ethno-cultural diversity which may present challenges for nursing practice. We performed an integrative review of literature published in North America and Europe between 1990 and 2007, to map the state of knowledge and to identify nursing assessment tools/models which are have an associated research or empirical perspective in relation to ethno-cultural dimensions of nursing care. Methods Data was retrieved from a wide variety of sources, including key electronic bibliographic databases covering research in biomedical fields, nursing and allied health, and culture, e.g. CINAHL, MEDline, PUBmed, Cochrane library, PsycINFO, Web of Science, and HAPI. We used the Critical Appraisal Skills Programme tools for quality assessment. We applied Torraco's definition and method of an integrative review that aims to create new knowledge and perspectives on a given phenomena. To add methodological rigor with respect to the search strategy and other key review components we also used the principles established by the Centre for Reviews and Dissemination. Results Thirteen thousand and thirteen articles were retrieved, from which 53 full papers were assessed for inclusion. Eight papers met the inclusion criteria, describing research on a total of eight ethno-cultural assessment tools/models. The tools/models are described and synthesized. Conclusions While many ethno-cultural assessment tools exist to guide nursing practice, few are informed by research perspectives. An increased focus on the efficiency and effectiveness of health services, patient safety, and risk management, means that provision of culturally responsive and competent health services will inevitably become paramount.